PELAKSANAAN PEMBEBASAN TANAH UNTUK PEMBANGUNAN JALAN JALUR 2 BYPSS KELURAHAN GAUNG KECAMATAN LUBEK BEGALUNG - Prasetyo, Ferry; Rianto, M.Pd, Slamet; Zuriyani, M.Si, Elvi (Pendidikan Geografi, 2014)
ABSTRACTThe purpose of this research is to get information, analyze and make description of data about : (1) The execution of land acquisition, (2) social economic and (3) problems from residents or goverment.This research was qualitatively by using interview technique. To answer this problem, used primary data was collected by observation, interview, discussion with resident and photos was taken on field, neanwhile secondary data was collected from related parties.Result of this research showed : (1) the influence of land acquisition execution for the resident, duration of the land acquisition process, thepayment of compensation to the resident and less financial of government, (2) since the execution of land acquisition, economic condition of resident is being dectrease, so that canât fulfii their life needs (3) problems that faced by resident or goverment are duration of the land acquisition process, payment of compensation to the resident and less financial hes not finished yet, based on the kind of building related with it.